Implications of Cancellation of Notification of An Appeal Decision Canceled By The Chairman of The Serang District Court - Desiliani, Melin; PS, Agus Prihartono; Agustina, Rani Sri (Jurnal Hukum Replik, 2024)
As a case breaker, the judge is assisted by court officials in handling a case, both the Substitute Registrar who accompanies the judge at trial, as well as the Bailiff/Alternate Bailiff who carries out the duties of adjudication and plays an important role in the proceedings at the Court. Bailiffs in carrying out their duties often face several obstacles/obstacles. The most crucial obstacle is the delivery of relaas through the headman. Bailiff/Substitute Advocate in making notification of the decision if the residence or residence of the parties is known, the notification of the decision is delivered directly to the disputing parties (in person), the term in person can be extended again to include the next of kin in a straight line up and down below (parents and children) or husband/wife. If the residence or residence of the person is known but neither is he or his family, a letter of notification shall be submitted to the local headman/Village Head. Relaas Summons/Notifications (Summons of the parties and notification of either a decision or a reprimand), is a very important instrument in civil proceedings because without a relaas the judge's decision cannot be justified and is not based on law. This study aims to find out the procedures for submitting notifications of appeal decisions and the implications of canceling the minutes of notification of appeal decisions that were canceled by the head of the Serang District Court. This study uses a normative juridical legal research method with a statutory approach based on secondary data supported by primary data and analyzed using a qualitative juridical method. The result of this research is the cancellation of the minutes of notification of the appeal decision which was canceled by the head of the Serang District Court resulting in the minutes of notification of the contents of the decision having to be re-executed because they were not submitted legally and properly due to procedural-administrative errors. The cancellation of the minutes of decision notification is carried out to correct errors that have occurred in order to avoid the potential to hinder the process of implementing the contents of the decision at a later date.Keywords: Implication, Cancellation, Minutes of Notification of Decision